2013
DOI: 10.3168/jds.2012-5682
|View full text |Cite
|
Sign up to set email alerts
|

Clinical endometritis in an Argentinean herd of dairy cows: Risk factors and reproductive efficiency

Abstract: The objectives of this study were to assess the clinical and metabolic risk factors for clinical endometritis, the likelihood for having a normal vaginal discharge during postpartum, and the effects of endometritis on milk yield, reproductive efficiency, and metabolic status in Holstein cows. The study was conducted in a commercial dairy herd (Cordoba, Argentina) where 303 Holstein cows were enrolled. Cows were body condition scored (1 to 5) and tail bled on -14, 7, 21, 31, 41, and 50 d relative to parturition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 38 publications
13
57
6
3
Order By: Relevance
“…The highest proportion of PMN was detectable in winter and the lowest in summer. The impact of seasonal effects on endometritis is unclear [52,55]. Whether weather or management associated factors were responsible for these results still needs to be elucidated [52,55,56].…”
Section: Discussionmentioning
confidence: 94%
“…The highest proportion of PMN was detectable in winter and the lowest in summer. The impact of seasonal effects on endometritis is unclear [52,55]. Whether weather or management associated factors were responsible for these results still needs to be elucidated [52,55,56].…”
Section: Discussionmentioning
confidence: 94%
“…Within a retrospective study of 102,060 dairy cows, Bruun et al (17) confirmed that dystocia was a risk factor that significantly increased the overall incidence of metritis and clinical endometritis during the first month after calving with an OR of 3.0 (95% CI: 2.3-4.0, P < 0.001) ( Table 2). Giuliodori et al (30) confirmed the correlation between abnormal calving and clinical endometritis with an adjusted OR of 2.2. Furthermore, dystocia indirectly increases the opportunity for the development of endometritis by increasing the probability of metritis with an OR of 4.3 (95% CI: 3.7-4.9, P < 0.001) (13).…”
Section: Dystociamentioning
confidence: 89%
“…Persistent uterine infection and clinical endometritis were less frequent in primiparous than multiparous cows since uterine involution was more rapid in the primiparous group (11). However, Giuliodori et al (30) and Thibier and Steffan (31) excluded an effect of the cow's age and parity number on the prevalence of clinical endometritis. Carneiro et al (16) reported that parity did not affect the incidence of subclinical endometritis.…”
Section: Intrinsic Factors 221 Parity Of the Cowmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for these uterine diseases mainly are problems around parturition and subsequent negative energy balance [46]. The most prevalent uterine pathogens isolated from cows with MET, CE, and in some cases SE are Escherichia coli and Trueperella pyogenes [7].…”
Section: Introductionmentioning
confidence: 99%